Visualization Tools for Monitoring and Debugging a Cognitive Architecture using CST - Marques, Aúreo; Coletta, Luiz [UNESP]; Silva, Anderson; Paraense, André; Berto, Letícia; Costa, Paula; Colombini, Esther; Simões, Alexandre [UNESP]; Gudwin, Ricardo (Elsevier, 2022)
In this work we address the use of visualization tools for developing intelligent agents built with Cognitive Architectures (CAs). Unfortunately, there are just a few discussions about this issue in the CAs literature. We start by bringing a summary on how this topic is currently being addressed within the community and further introduce our efforts in building visualization tools for both debugging and aiding the understanding of the inner mechanisms of a CA. For this, we propose the MindViewer, a visualization tool for monitoring and debugging CAs constructed with CST, the Cognitive Systems Toolkit. MindViewer encompasses a variety of charts that are used to monitor the inner details of the agents' mind. Its Web version allows inspect even complex data structures and customize their generated graphics. We exemplify their capabilities through a experimental application based on a robot simulation inspired in Iowa Gambling Task.
Keywords: Cognitive Architectures Development; Debugging; Mind Viewers; Visualization Tools